2017
DOI: 10.1371/journal.pone.0185836
|View full text |Cite
|
Sign up to set email alerts
|

Functional indicators of response mechanisms to nitrogen deposition, ozone, and their interaction in two Mediterranean tree species

Abstract: The effects of nitrogen (N) deposition, tropospheric ozone (O3) and their interaction were investigated in two Mediterranean tree species, Fraxinus ornus L. (deciduous) and Quercus ilex L. (evergreen), having different leaf habits and resource use strategies. An experiment was conducted under controlled condition to analyse how nitrogen deposition affects the ecophysiological and biochemical traits, and to explore how the nitrogen-induced changes influence the response to O3. For both factors we selected reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 85 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…The temporarily higher PI under O 3 stress in August indicated an enhanced efficiency of electron trapping and transport which might be related to the repair processes (Bussotti et al 2011). Nitrogen addition ameliorated the O 3 -induced decrease of F v /F m and PI in July as previously observed in aspen (Häikiö et al 2007) and manna ash (Fusaro et al 2017). Nitrogen-fertilized plants are considered more tolerant to photoinhibition due to their higher photosynthetic energy consumption (e.g.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The temporarily higher PI under O 3 stress in August indicated an enhanced efficiency of electron trapping and transport which might be related to the repair processes (Bussotti et al 2011). Nitrogen addition ameliorated the O 3 -induced decrease of F v /F m and PI in July as previously observed in aspen (Häikiö et al 2007) and manna ash (Fusaro et al 2017). Nitrogen-fertilized plants are considered more tolerant to photoinhibition due to their higher photosynthetic energy consumption (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Braun et al (2017) reported that the basal area increment in beech and Norway spruce may be limited by O 3 and that a significant interaction exists with nutrition such as N and P. However, our knowledge of plant responses to O 3 under various nutritional conditions is still limited. Only a few studies have investigated the effects of different N loads on O 3 sensitivity in terms of photosynthetic traits, with mitigating (Fusaro et al 2017;Häikiö et al 2007;Watanabe et al 2006), detrimental Yamaguchi et al 2007) and neutral effects (Feng et al 2011;Harmens et al 2017). To our knowledge, the interaction between N, P and O 3 on photosynthetic traits has never been tested.…”
Section: Physiological Ecology Of Woody Species In Response To Air Po...mentioning
confidence: 99%
“…The species-specificity in response to the combined effect of elevated [O 3 ] and nitrogen supply was reported by Fusaro et al [187] for two Mediterranean tree species. Nitrogen supply ameliorated the harmful effects of O 3 in deciduous manna ash (Fraxinus ornus), but not in evergreen holm oak (Quercus ilex).…”
Section: Interactive Effect Of Nitrogen Supply and Osupporting
confidence: 64%
“…Consequently, the plant photosynthetic performance is reduced, as highlighted by the significant decrease of PI TOT in both T1200 mg kg −1 and T360 mg kg −1 . This represents a conservative photoprotective strategy (Bussotti et al 2020 ), which prevents irreversible injuries to the photosynthetic apparatus when photosynthesis is limited by environmental stress factors, as described in plants exposed to drought (Oukarroum et al 2007 ; Strasser et al 2010 ; Salvatori et al 2016 ), salt stress (Fusaro et al 2014 ; Kalaji et al 2018 ), heavy metals (Bernardini et al 2016 ), or tropospheric ozone (Bussotti et al 2011 ; Salvatori et al 2013 , 2015 ; Fusaro et al 2017 ). In our case, the observed PSII downregulation was likely triggered by the capacity of SLES to interfere with water and/or nutrients uptake by roots, in agreement with what is observed for root elongation in the germination test.…”
Section: Discussionmentioning
confidence: 99%